2023
DOI: 10.1038/s41467-023-37742-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-component multilayered self-assembling protein nanoparticles presenting glycan-trimmed uncleaved prefusion optimized envelope trimers as HIV-1 vaccine candidates

Abstract: Uncleaved prefusion-optimized (UFO) design can stabilize diverse HIV-1 envelope glycoproteins (Envs). Single-component, self-assembling protein nanoparticles (1c-SApNP) can display 8 or 20 native-like Env trimers as vaccine candidates. We characterize the biophysical, structural, and antigenic properties of 1c-SApNPs that present the BG505 UFO trimer with wildtype and modified glycans. For 1c-SApNPs, glycan trimming improves recognition of the CD4 binding site without affecting broadly neutralizing antibodies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(69 citation statements)
references
References 171 publications
9
60
0
Order By: Relevance
“…Additionally, the M2ex3 FR and I3-01v9a SApNPs also showed 45–86 times greater accumulation compared with the M2ex3 trimer at 1 week (Figure F). These results are consistent with our previous findings, ,, in which small particles (<15 nm) were cleared from lymph node follicles within 48 h, whereas large particles (30–100 nm) remained for weeks. Importantly, M2ex3 I3-01v9a and BG505 Env I3-01v9 SApNPs showed significantly longer follicular retention than the SARS-CoV-2 spike-presenting I3-01v9 SApNP (∼8 weeks vs ∼2 weeks), , suggesting a correlation between SApNP retention and antigen thermostability (a T m value of 65 °C or greater for M2ex3 and BG505 Env vs 48 °C for SARS-CoV-2 spike).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Additionally, the M2ex3 FR and I3-01v9a SApNPs also showed 45–86 times greater accumulation compared with the M2ex3 trimer at 1 week (Figure F). These results are consistent with our previous findings, ,, in which small particles (<15 nm) were cleared from lymph node follicles within 48 h, whereas large particles (30–100 nm) remained for weeks. Importantly, M2ex3 I3-01v9a and BG505 Env I3-01v9 SApNPs showed significantly longer follicular retention than the SARS-CoV-2 spike-presenting I3-01v9 SApNP (∼8 weeks vs ∼2 weeks), , suggesting a correlation between SApNP retention and antigen thermostability (a T m value of 65 °C or greater for M2ex3 and BG505 Env vs 48 °C for SARS-CoV-2 spike).…”
Section: Resultssupporting
confidence: 94%
“…In summary, hM2e can be successfully displayed on all three SApNPs, consistent with our previous studies where stabilized HIV-1, ,, HCV, EBOV, and SARS-CoV-1/2 , antigens were displayed on the surface of SApNPs. Extensive biochemical, biophysical, structural, and antigenic characterizations provided detailed in vitro profiles of hM2e-presenting SApNPs, thus allowing evaluation of these vaccine immunogens in vivo.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The authors accomplished this in one of two ways, either through an extended dosing schedule or via using different NP versions of HIV env. Similar results also were observed using HIV env in a different study by Zhang et al 133 The authors in the Zhang et al showed that two different NP versions of HIV env were retained for 420 times longer in FDCs and thereby elicited much stronger germinal centre reactions, a key component of protective immunity. The fact that two separate groups showed that protein-based NPs facilitate targeting to FDCs where antigen retention is enhanced and leads to robust B cell recognition of the intact antigen is an intriguing finding that highlights the potential of protein NP-based vaccines as a platform to increase the potency of subunit vaccines.…”
Section: Nps Antigen Retention and The Immune Responsesupporting
confidence: 81%
“…A third type of particulate assembly that has been developed more recently for use in vaccines is protein-based NPs. NP platforms for the multivalent display of vaccine antigens have proven effective in boosting immunogenicity for antigens such as Ebola GP, 130 HIV env, [131][132][133] SARS CoV-2 spike, 134 RSV F, 135 and influenza haemagglutinin. 136…”
Section: Virus-like Particlesmentioning
confidence: 99%